Applications of Genetically Engineered Microorganisms in Medicine, Food, Environment and Agriculture - Benjamin, Gideon Yakusak; Benjamin, Rejoice Ziriyi (FUDMA Journal of Sciences, 2026)
Genetic engineering is the artificial manipulation and recombination of DNA or other nucleic acid molecules in order to alter the genetic makeup of an organism, typically to introduce or modify specific traits. Different types of genetically engineered microorganisms (GEMs) have been developed through recombinant DNA and RNA technologies; these have been applied in the field of medicine, food industry, environment and agriculture. GEMs have been utilized in medicine for the production of antibiotics, vaccines and heterologous proteins such as insulin. Microorganisms are used in food production either as integral parts in the preparation of various fermented foodstuffs or to produce food additives and processing aids (organic acids, flavouring agents, food enzymes etc.).  Modifications are made to the genetic makeup of microorganisms to either produce a new protein or other food ingredient, to improve or enhance the production of an existing protein/ingredient, or to tailor the characteristics of an existing protein to a new application. Genetically engineered microorganisms can be used for the bioremediation of polluted soils and therefore increase soil productivity. They can also be used as bio-detectors to monitor soil pollution so that it can be managed more efficiently or prevented. They can also enhance nitrogen fixation and nutrient uptake in the soil. Microbial biological control agents (MBCAs) are an example of GEMs that could be used in agricultural practices to make them more environmentally friendly and less polluting. The present study reviews the applications of genetically engineered microorganisms in medicine, environment, food and agriculture.
Keywords: Genetic; Transgenic; Microorganisms; Agriculture; Environment